Respon Pertumbuhan Tanaman Pakcoy (Brassica chinensis L.) Terhadap Aplikasi Pupuk Organik Cair (POC) Limbah Buah-Buahan - Ramadanis, Viona; Amelia, Kiki; Putri, Santi Diana; Sari, Wilna (JURNAL AGROPLASMA, 2024)
Pakcoy (Brassica chinensis L.) is one type of vegetable that has many benefits, and this plant is one of the commodities with high economic value. Pakcoy plant production is still low because Indonesian people have not cultivated it much because there are several obstacles faced, one of which is soil fertility. In general, to overcome soil fertility, farmers usually only apply inorganic fertilizers. The main purpose for applying inorganic fertilizers is to increase the availability of nutrients quickly in the soil so that it can meet the nutrient needs of plants, but by applying inorganic fertilizers it cannot improve the physical and biological properties of the soil, and when using inorganic fertilizers it can damage the soil. The purpose of this study was to determine the growth response of pakcoy plants to the application of fruit waste POC. The research was conducted in the experimental garden of the Department of Agroindustry, Padang State University in Sijunjung Regency with an altitude of ±450 meters above sea level. This research was conducted in April  - June 2023. The design used in this study was a Randomized Group Design (RAK) with 4 treatments and 6 replicates totaling 24 experimental samples. The treatments given in this study were P0 control (without treatment), P1 150 ml/L water POC fruits, P2 250 ml/L water POC fruits, P3 350 ml/L water POC fruits. The research data were analyzed using anova table 5% and continued with DMRT further test. The parameters observed were plant height, number of leaves, leaf width, stump diameter, and wet weight. Based on the results of the research on the growth response of pakcoy (Brassica chinensis L.) plants to the application of liquid organic fertilizer (POC) fruits, it can be concluded that the P2 treatment (250 ml / plant) produces the highest average value in plant height growth which is 28 cm, the number of leaves is 23 strands, leaf width is 9 cm, the diameter of the stem is 20 cm, and the wet weight of the plant is 138 grams. While the lowest average value is in the P0 treatment (without giving POC / control) which produces plant height growth of 24 cm, the number of leaves is 15 strands, the width of the leaves is 7 cm, the diameter of the stem is 18 cm and the wet weight of the plant is 87 grams. Keywords: growth, pakcoy, poc, fruit waste, organic